Fuga da promessa e nostalgia do divino: a antropologia de Dom Casmurro de Machado de Assis como tema no diálogo entre teologia e literatura - Conceição, Douglas Rodrigues da (2003)
The principle concern of this research resides in the dialogue between theology and literature, primarily in terms of the novel Dom Casmurro, by Machado. The dissertation takes the emergent anthropology in the machadian novel under consideration as a space of theological reflection. In terms of the general discussion, referential works are presented that describe the current state of the question regarding the dialogue between theology and literature. Theoretical support for the research is provided through the appropriation of concepts in Paul Ricoeur, Antonio Carlos de Melo Magalhães and Gerard Genette. Nonetheless, the objective of this research is limited to the demonstration of the relations between the God that reveals himself and the machadian human, based on the anthropological character of the romance Dom Casmurro. The promise and the para-texual character of the chapter, in that it is narrated, guide the analyses realized, which culminates with the observation that the anthropologic is the central theme of the novel. We defend that the rupture of relations established between the machadian human and the God of the promise, expressed in the existence and reality of the protagonist of the novel, Bento Santiago, established a disenchanted world.(AU)